2018
DOI: 10.1525/abt.2018.80.5.339
|View full text |Cite
|
Sign up to set email alerts
|

The Pet Plant Project: Treating Plant Blindness by Making Plants Personal

Abstract: “Plant blindness” is defined as the failure to appreciate the fundamental importance of plants. To address this phenomenon, we created the Pet Plant Project (P3) where students grow an unknown plant from seed, monitor development, and relate lecture concepts to their plant on a daily basis. A qualitative survey was administered and analyzed to evaluate student responses to the experience. Themes in the analysis, identified across 209 student-participants at Tennessee Tech University, included positive reinforc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(27 citation statements)
references
References 20 publications
1
16
0
3
Order By: Relevance
“…In a study in which over 4000 children aged 8-16 participated (Lindemann-Matthies 2005), it was found that the students' interest in wild plants increased after an educational programme focusing on wild plants in the nearby environment. Another project where students grew plants from a seed to a mature plant showed that students' relationships with plants were strengthened (Krosnick, Baker and Moore 2018). Similar findings have been reported from a study (Nyberg and Sanders 2014), in which a delayed post-test, 6 months after the project, however, demonstrated that students' increased interest appeared to be time-limited.…”
Section: Introductionsupporting
confidence: 80%
“…In a study in which over 4000 children aged 8-16 participated (Lindemann-Matthies 2005), it was found that the students' interest in wild plants increased after an educational programme focusing on wild plants in the nearby environment. Another project where students grew plants from a seed to a mature plant showed that students' relationships with plants were strengthened (Krosnick, Baker and Moore 2018). Similar findings have been reported from a study (Nyberg and Sanders 2014), in which a delayed post-test, 6 months after the project, however, demonstrated that students' increased interest appeared to be time-limited.…”
Section: Introductionsupporting
confidence: 80%
“…This mirrors much of the research work in educational science that concerns questions of preference for animals or plants (e.g., Wandersee, ; Kinchin, ); student responses to diverse plant education interventions (e.g., Lindemann‐Mathies, ; Fančovičová, & Prokop, ; Nyberg & Sanders, ; Krosnick, Baker, & Moore, ; Pany et al, ); student reactions to specific plant displays in botanic gardens (e.g., Tunnicliffe, ; Sanders, ); considerations of plants in science curricula content (e.g., Hershey, ; Galbraith, ; Ebert‐May & Holt, ); and the relatively few visual cognition studies concerned with plants (e.g., Schussler and Olzak, ; Balas & Momsen, ). Furthermore, a large body of educational research has concerned itself with the identification of plants and the perceived connections between knowledge of, and attitudes to, plants (e.g., Bebbington, ; Frisch, Unwin, & Saunders, ).…”
Section: Introductionmentioning
confidence: 60%
“…Integrating plant-based knowledge in K-12 curricula, as well as in college-level general biology education, could include teaching about specific "flagship species" that students show interest in, such as those used for medicinal purposes (Pany & Heidinger, 2017). Hands-on plant-growing projects could be used that coincide with lessons over the course of a unit or semester, such as school gardens (Waliczek & Zajicek, 1999) or the Pet Plant Project (Krosnick et al, 2018), which encourages integration with lessons as well as identification and care of plants by students.…”
Section: Science Majors Before and After The Gardening Activitymentioning
confidence: 99%